Study of Influence of Customer Relationship Management on Customer Satisfaction in CV Batik Semarang16 - Shofiah, Siti; Sukresna, I Made; Sugiono, Sugiono (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2017)
This study aimed to examine the influence of customer relationship management on customer satisfaction, with product innovation Â and customer value as mediating variables. The study conducted in Batik Semarang16.The samples were customers of Batik Semarang16, a total of 126 respondents. Structural Equation Modeling (SEM) run by AMOS software was used to analyze the data. The analysis showed that customer relationship management, product innovation and customer value had positive influence on customer satisfaction.The empirical findings indicated that customer relationship management positively influenced product innovation; customer relationship management positively influenced customer value; product innovation positively influenced customer satisfaction; and customer value influenced customer satisfaction.